Radiation tolerance studies of the HV-mux GaNFETs for the HL-LHC ATLAS ITk Strip detector. (1st April 2023) - Capocasa, F.; Fielitz, W.; Gutierrez Zagazeta, L.F.; Kierstead, J.; Lynn, D.; Musso, C.; Stucci, S.
Abstract: For the High-Luminosity upgrade of the LHC, the current ATLAS inner detector will be replaced with a new silicon charged-particle tracker, the ITk, which consists of the ITk Pixel and the ITk Strip subdetector. The high voltage multiplexing (HV-Mux) GaNFETs are radiation-tolerant transistors that permit switching off high voltage to malfunctioning sensors on the ITk Strip modules. To ensure the reliability of the GaNFETs in the high radiation environment expected at the HL-LHC, a sample of the production batch was exposed to gamma radiation. The GaNFETs were characterized pre-irradiation and post-irradiation, and monitored during irradiation.